2005
DOI: 10.1073/pnas.0408378102
|View full text |Cite
|
Sign up to set email alerts
|

An embryonic poly(A)-binding protein (ePAB) is expressed in mouse oocytes and early preimplantation embryos

Abstract: Gene expression during oocyte maturation, fertilization, and early embryo development until zygotic gene activation is regulated mainly by translational activation of maternally derived mRNAs. This process requires the presence of a poly(A)-binding protein. However, the cytoplasmic somatic cell poly(A)-binding protein (PABP1) is not expressed until later in embryogenesis. We recently identified an embryonic poly(A)-binding protein (ePAB) in Xenopus. ePAB is the predominant cytoplasmic PABP in Xenopus oocytes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
121
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(131 citation statements)
references
References 59 publications
7
121
2
1
Order By: Relevance
“…Cold Spring Harbor Laboratory Press on March 23, 2019 -Published by genesdev.cshlp.org Downloaded from ePABP has been characterized in Xenopus and mouse (Voeltz et al 2001;Seli et al 2005) and is ∼70% identical at the amino acid level to classical PABP, with the most marked differences near the C terminus. Since this region is essential for interaction with PABP-specific regulators that can modulate function, truncation as well as variations in the C-terminal region of ePABP relative to PABP may define novel roles.…”
Section: Translation Regulatory Cascades Genes and Development 141mentioning
confidence: 99%
See 1 more Smart Citation
“…Cold Spring Harbor Laboratory Press on March 23, 2019 -Published by genesdev.cshlp.org Downloaded from ePABP has been characterized in Xenopus and mouse (Voeltz et al 2001;Seli et al 2005) and is ∼70% identical at the amino acid level to classical PABP, with the most marked differences near the C terminus. Since this region is essential for interaction with PABP-specific regulators that can modulate function, truncation as well as variations in the C-terminal region of ePABP relative to PABP may define novel roles.…”
Section: Translation Regulatory Cascades Genes and Development 141mentioning
confidence: 99%
“…Yet, PABP and ePABP have been demonstrated to be interchangeable for many PABP functions, including rescue of a pab1⌬ lethality in Saccharomyces cerevisiae, interactions with the cap-binding eIF4G complex, and with termination factor eRF3, poly(A), and AU-rich element binding, as well as preventing deadenylation of the mRNA (Voeltz et al 2001;Cao and Richter 2002;Cosson et al 2002). A feature that distinguishes ePABP from the normal cytoplasmic PABP is its expression pattern: ePABP has so far been found to be expressed exclusively in an oocyte-and embryo-specific manner (Voeltz et al 2001;Seli et al 2005). The realization that ePABP is the predominant PABP present during oocyte maturation and early embryogenesis in both Xenopus and mouse begs the question of how it may function differently from cytoplasmic PABP, which replaces it later in development.…”
Section: Translation Regulatory Cascades Genes and Development 141mentioning
confidence: 99%
“…Notably, in a recently published study, the EPAB mRNA being transcribed in the human somatic cells and 8-cell and blastocyst stage early embryos includes a premature stop codon in the exon 8 [30]. In marked contrast, mouse Epab is found to be transcribed only in the ovary and testis tissues, but not in the somatic tissues [25]. Further analysis on the postnatal mouse testes and isolated spermatogenic cells showed that it is expressed solely in the spermatogenic cells, and exhibits prominent expressional differences during testicular development [26], and in the postnatal mouse ovaries [32].…”
Section: Discussionmentioning
confidence: 94%
“…The embryonic poly(A)-binding protein (EPAB, also known as ePABP and PABPc1-like), is expressed in mouse [25,26] and human [27] gonads. In the postnatal mouse testes, Epab mRNA expression is localized to only spermatogenic cell types, but it is not expressed in the somatic cells [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation